Azadirachta indica A. Juss Ameliorates Mouse Hepatitis Virus-Induced Neuroinflammatory Demyelination by Modulating Cell-to-Cell Fusion in an Experimental Animal Model of Multiple Sclerosis - Sarkar, Lucky; Putchala, Ravi Kiran; Safiriyu, Abass Alao; Das Sarma, Jayasri (Frontiers in Cellular Neuroscience, 2020)
Mouse hepatitis virus (MHV)-induced murine neuroinflammation serves as a model to study acute meningoencephalomyelitis, hepatitis, and chronic neuroinflammatory demyelination; which mimics certain pathologies of the human neurologic disease, multiple sclerosis (MS). MHV-induced acute neuroinflammation occurs due to direct glial cell dystrophy instigated by central nervous system (CNS)-resident microglia and astrocytes, in contrast to peripheral CD4+T cell-mediated myelin damage prevalent in the experimental autoimmune encephalomyelitis (EAE) model of MS. Viral envelope Spike glycoprotein-mediated cell-to-cell fusion is an essential mechanistic step for MHV-induced CNS pathogenicity. Although Azadirachta indica (Neem), a traditional phytomedicine, is known for its anti-inflammatory, anti-fungal, and spermicidal activities, not much is known about anti-neuroinflammatory properties of its bark (NBE) in MHV-induced acute neuroinflammation and chronic demyelination. Recombinant demyelinating MHV strain (RSA59) was preincubated with NBE to arrest the infection-initiation event, and its effect on viral replication, viral transcription, cytokine expression, and successive pathogenicity were investigated in vitro and in vivo. Virus-free Luciferase assay explained NBE’s anti-virus-to-cell fusion activity in vitro. Intracranial inoculation of RSA59 preincubated with NBE into the mouse brain significantly reduces acute hepatitis, meningoencephalomyelitis, and chronic progressive demyelination. Additionally, NBE effectively restricts viral entry, dissemination in CNS, viral replication, viral transcription, and expression of the viral nucleocapsid and inflammatory cytokines. From mechanistic standpoints, RSA59 preincubated with NBE reduced viral entry, viral replication and cell-to-cell fusion, as a mode of viral dissemination. Moreover, intraperitoneal injection with NBE (25 mg/kg B.W.) into mice revealed a significant reduction in viral Nucleocapsid protein expression in vivo. Conclusively, A. indica bark extract may directly bind to the virus-host attachment Spike glycoprotein and suppresses MHV-induced neuroinflammation and neuropathogenesis by inhibiting cell-to-cell fusion and viral replication. Further studies will focus on combining bioanalytical assays to isolate potential NBE bioactive compound(s) that contribute towards the anti-viral activity of NBE.